Electrostatic Dual-Layer Solvent-Free Cathodes for High-Performance Lithium-Ion Batteries - Haojin Guo; Chengrui Zhang; Yujie Ma; Ning Liu; Zhifeng Wang (Energies, 2025)
Slurry-cast (SLC) electrode manufacturing faces problems such as thickness limitation and material stratification, which are caused by applying toxic organic solvents. Solvent-free electrode technology, as a sustainable alternative, could get rid of issues generated by solvents. In this study, dual-layer NCM811 solvent-free electrodes (DLEs) are fabricated via an electrostatic powder deposition method with an active material-rich upper layer to provide high energy output, while the more binder–conductor content base layer improves conductivity and contact with current collectors. The dual-layered structure overwhelms the single-layer electrode (SE) with stable cycling performance caused by more regulated pore structures. DLE maintains 74% capacity retention after 100 cycles at 0.3 C, while the SLC shows only 60% capacity retention. Additionally, DLE shows excellent rate performance at various rates, with 207.3 mAh g−1, 193.9 mAh g−1, 173.9 mAh g−1, 157.3 mAh g−1, and 120.4 mAh g−1 at 0.1 C, 0.2 C, 0.5 C, 1.0 C, and 2.0 C, respectively. The well-designed DLE cathodes exhibit superior discharge-specific capacities, rate performance, and improved cycling stability than traditional SLC cathodes. It enlightens the path toward new structure innovations of solvent-free electrodes.